A comprehensive review of the truck appointment scheduling models and directions for future research. Issue 1 (2nd January 2022) - Abdelmagid, Ahmed Mohssen; Gheith, Mohamed Samir; Eltawil, Amr Bahgat
ABSTRACT: The performance of a container terminal is typically evaluated using two main indicators: the vessel berthing time and the truck turnaround time. These two indicators are significantly influenced by the truck's arrivals and departures to/from the container terminal. In the truck appointment scheduling problem, it is desired to designate a time slot for each truck to pick up/deliver a container from/to the container terminal while considering the objectives and constraints of the terminal and the trucking companies. Truck appointment systems are considered as a solution to control the truck arrivals and improve terminal efficiency. This paper presents a comprehensive review and analysis of the literature addressing the external truck appointment scheduling problem and presents possible directions for future research. After explaining the problem and its importance, the reviewed literature is classified based on three main categories: control and decision perspectives, modelling methodologies, and collaboration between stakeholders. Furthermore, the impact of implementing information and communication technologies on the external truck appointment scheduling problem is addressed. The paper covers the most recent publications and discusses their contributions. Besides, research gaps and future research directions are concluded.